Transformation of The Interpretation of The Cut Hand Verse for The Relevance of Contemporary Islamic Law: A Study of QS. Al-Maidah: 38 - Mukhorobin, Muhammad Abdul Aziz; Nugroho, Kharis (Universitas Muhammadiyah Surakarta, 2025)
This study aims to analyze the transformation of QS interpretation. Al-Māidah: 38 on the punishment of cutting off the hands of thieves, by tracing the dynamics of classical tafsir based on fiqh tafsir and tafsir bil ma'tsūr and their relevance within the framework of contemporary Islamic law through the Maqāṣid al-Sharī'ah approach. This research uses a qualitative design with a library research method. Data were collected from classical sources of interpretation, fiqh literature, and relevant contemporary Islamic law studies, then analyzed using descriptive-analytical and comparative approaches to identify patterns of interpretation, legal principles, and paradigm shifts in the meaning of hudūd theft. The results of the study show that QS. Al-Māidah:38 is not understood textually and absolutely in the classical tradition, but is rather limited by strict conditions such as niṣāb, proof, intention, and the absence of emergency conditions. The historical practice of the Companions, especially the policy of Umar ibn al-Khattab, confirms that consideration of welfare and social justice is the main factor in the implementation of hudūd. In contemporary discourse, the approach of Maqāṣid al-Sharī'ah reinforces the substantial orientation of Islamic law by placing the protection of property, human dignity, and social welfare as the main goals, thus opening up space for a contextual and humanist reinterpretation of hudūd. This study concludes that the transformation of QS interpretation. Al Māidah: 38 is part of the ongoing dynamics of ijtihad of Islamic law, as well as making an important contribution to the development of Islamic criminal law that is relevant, just, and responsive to modern social realities.